The Association of Physical Symptoms and Psychological Problems in the Indonesian Community During the COVID-19 Outbreak - Heni Dwi Windarwati; Budi Anna Keliat; Dayat Trihadi; Mochamad Ali Sodikin; Tjahjanti Kristaningsih; Mohammad Fatkhul Mubin; Akemat Akemat; Thika Marliana; Lahargo Kembaren; Niken Asih Laras Ati; Shofi Khaqul Ilmy; Ari Dwi Sulaksono; et al. (Journal of Caring Sciences)
Introduction: Changes in health status and adjustments to new lifestyles during the pandemic have triggered societal psychological problems in society. This study aimed to explore the correlation between physical symptoms and psychological problems in Indonesian society during the COVID-19 outbreak. Methods: This cross-sectional study employed an online survey to gather data from 9425 participants in Indonesia between June and July 2020, which was selected using convenience sampling. The Self-Reporting Questionnaire (SRQ) instrument was employed to investigate psychological problems, the utilization of psychoactive substances, psychotic symptoms, and post-traumatic stress disorder (PTSD). Physical symptoms were assessed through self-reports indicating the presence or absence of experienced COVID-19 symptoms. The statistical analyses were conducted using Spearman-rank and Cramer’s V correlation. Results: The findings suggest that the perceived physical symptoms during the COVID-19 outbreak are significantly associated with psychological problems, (including decreased energy, somatic symptoms, depressive moods, and depressive thoughts, the use of psychoactive substances, psychotic symptoms, and PTSD. Conclusion: Our study concluded that physical health is significantly associated with psychological problems. It is essential to eliminate factors that cause psychological problems by promoting the physical condition of the general population. Through promotive and preventive efforts, physical and psychological conditions should be improved in COVID-19 outbreaks.